Atypical Distant Metastasis of Breast Malignant Phyllodes Tumors: A Case Report and Literature Review - Tiphaine de Foucher; Hélène Roussel; Mikael Hivelin; Léa Rossi; Caroline Cornou; Anne-Sophie Bats; Myriam Deloménie; Fabrice Lécuru; Charlotte Ngô (Case Reports in Obstetrics and Gynecology)
Malignant phyllodes tumors (MPT) are rare breast neoplasms. Preoperative diagnosis is often challenging due to the unspecific clinical, radiological, and histological characteristics of the tumor. Dissemination pathways are local with chest wall invasion, regional with lymph nodes metastasis, and distant, hematogenous, mostly to the lungs, bones, and brain. Distant metastasis (DM) can be synchronous or appear months to years after the diagnosis and initial management. The current report describes the case of a 57-year-old woman presenting with a giant/neglected MPT of the breast, with no DM at initial staging, treated by radical modified mastectomy. Motor disorders due to medullar compression by a paravertebral mass appeared at short follow-up, also treated surgically. The patient died from several DM of rapid evolution. To our knowledge, this is the only case described of MPT with metastases to soft tissue causing medullar compression. We present a literature review on unusual metastatic localizations of MPT.